Heavy Metal Removal Technologies with Details of Ion Exchange: ‎Review study (Journal of University of Babylon for Engineering Sciences, 2024)
Heavy metals are currently recognized as one of the most serious environmental challenges, as well as one of the most dangerous environmental contaminants. Due to these metals' toxicity, inability to biodegrade, and tendency to accumulate in organisms and enter the human food chain, they are responsible for a wide range of diseases. Many techniques, including chemical precipitation, membrane filtration, coagulation and flocculation, flotation, electrochemical methods, adsorption, and ion exchange, can be used to remove heavy metal ions from wastewater. several key factors should be considered to ensure effective and efficient treatment methods such as effectiveness, cost, scalability, compatibility with wastewater characteristics, residual management, and environmental impact. A detailed explanation of the ion exchange method was provided because this technique shows great promise in terms of selectivity, availability, thermal stability, chemical compatibility, ionic capacity, and regeneration capability. This study will contribute to the field of sustainable materials science and environmental remediation.